A Taxonomic Revision of the Neotropical Genus Martiodendron (Fabaceae: Dialioideae) - Falcão, Marcus José De Azevedo; Torke, Benjamin M.; Garcia, Gabriel Santos; Da Silva, Guilherme Sousa; Mansano, Vidal De Freitas (Phytotaxa, 2023)
Martiodendron (Leguminosae/Fabaceae) is a Neotropical genus of trees and shrubs comprising five species. It is characterized by its yellow pentamerous corolla, four to five long poricidal anthers and large, attractive red samaras; it represents an intermediate stage of floral reduction among the 17 genera of the subfamily Dialioideae, which display diverse floral morphologies including different types of reduced flowers in the perianth and androecium. The last taxonomic revision of Martiodendron was published some 60 years ago and there is frequent misidentification of specimens in herbaria, databases, and floristic works with mistreatment of taxa and unclear geographic distributions. Thus, circumscriptions of the species and varieties of the genus require reassessment in light of the substantial new data that has become available during the last several decades. Here, we synthesized morphological, geographical, and ecological data on the genus to produce a modern integrative taxonomic treatment. Our taxonomic concepts are underpinned by analysis of 352 herbarium specimens and substantial fieldwork in South America. We recognize five species and four varieties of Martiodendron. All of these taxa display high levels of morphological and geographical cohesion. One of the varieties, M. mediterraneum var. concinnum, is described as new to science. Detailed descriptions of each recognized taxa are accompanied by illustrations, distribution maps, conservation status assessments, and complete nomenclatural treatments with four new lectotypifications. An identification key and a morphometric analysis of fruits are also provided.